2019
DOI: 10.1007/s00228-019-02707-z
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to psychotropic medication in completed suicide in Sweden 2006–2013: a forensic-toxicological matched case-control study

Abstract: Objective To investigate the influence of adherence to psychotropic medications upon the risk of completed suicide by comparing person-level prescriptions and postmortem toxicological findings among complete-suicide cases and non-suicide controls in Sweden 2006-2013. Methods Using national registries with full coverage on dispensed prescriptions, results of medico-legal autopsies, causes of death, and diagnoses from inpatient care, estimated continuous drug use for 30 commonly prescribed psychotropic medicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…According to the data obtained from the National Institute of Statistics (INE) in Spain, the number of suicides is higher in men than in women. These data correlate with those of the present study and those carried out in recent years in Spain [38] and Europe [21,[56][57][58].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…According to the data obtained from the National Institute of Statistics (INE) in Spain, the number of suicides is higher in men than in women. These data correlate with those of the present study and those carried out in recent years in Spain [38] and Europe [21,[56][57][58].…”
Section: Discussionsupporting
confidence: 94%
“…The associations between psychotropic medications and the risk of suicide are a recurring topic of discussion [18,19]. Antipsychotic agents appear to have protective effects in both non-fatal suicides and complete suicidal acts, but the possible anti-suicide or pro-suicide properties of antidepressants remain inconclusive [20][21][22][23]. Nevertheless, it was observed that people treated with medications were 9.6 times more likely to attempt suicide during the hours they were intoxicated [24].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, one could wonder if the routine blood level monitoring for antipsychotics may thus contribute to its superior effectiveness in previously non-responsive patients (Patteet et al, 2012 ). Moreover, non-adherence has been significantly associated with poorer clinical outcome, including greater risk of hospitalization, longer duration of hospitalization (Higashi et al, 2013 ; Olivares et al, 2013 ), and greater risk of suicide (Leucht and Heres, 2006 ; Llorca, 2008 ; Forsman et al, 2019 ). In addition, partial and total medication non-adherence are strongly associated with psychotic relapse as non-adherent patients with schizophrenia having a 5-fold increase in risk of relapse (Robinson et al, 1999 ; Caseiro et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, non-adherence to antipsychotic medication has been shown to be associated with a higher rate of psychiatric and medical hospitalizations in patients with schizophrenia [130]. Biochemically verified non-adherence to antipsychotic medication was reported to be associated with an increased risk of completed suicide [131]. In the USA in 2016, the estimated cost of drug-related morbidity and mortality resulting from non-optimized pharmacotherapy, including medication non-adherence, was USD 528 billion [132].…”
Section: Digital Medicine Systemmentioning
confidence: 99%